Reflections on directing 25 years of the annual transition conference - Albert C. Hergenroeder (Health Care Transitions)
Albert C. Hergenroeder, MD, Professor of Pediatrics, Chief, Adolescent Medicine and Sports Medicine, Baylor College of Medicine The paper is based on the author’s opening address for the 25th annual Chronic Illness and Disability: Transition from Pediatric to Adult-based care conference at Baylor College of Medicine/Texas Children’s Hospital conference delivered October 10, 2024